2009
DOI: 10.1185/03007990903437412
|View full text |Cite
|
Sign up to set email alerts
|

Switching from oral extended-release methylphenidate to the methylphenidate transdermal system: continued attention-deficit/hyperactivity disorder symptom control and tolerability after abrupt conversion

Abstract: Objective To evaluate symptom control and tolerability after abrupt conversion from oral extended-release methylphenidate (ER-MPH) to methylphenidate transdermal system (MTS) via a dose-transition schedule in children with attention-deficit/hyperactivity disorder (ADHD). Methods In a 4-week, prospective, multisite, open-label study, 171 children (164 intent-to-treat) with diagnosed ADHD aged 6–12 years abruptly switched from a stable dose of oral ER-MPH to MTS in nominal dosages of 10, 15, 20, and 30 mg usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Of 34 publications included in the review, three publications derived from two open-label switching studies [ 46 - 48 ] and three publications derived from one observational study [ 49 - 51 ] were identified. All studies included Concerta ® as a comparator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 34 publications included in the review, three publications derived from two open-label switching studies [ 46 - 48 ] and three publications derived from one observational study [ 49 - 51 ] were identified. All studies included Concerta ® as a comparator.…”
Section: Resultsmentioning
confidence: 99%
“…Titration was based on changes in ADHD-RS-IV score and Clinical Global Impressions–Severity (CGI–S) scale score. Measures of ADHD symptoms and quality of life were obtained using ADHD-RS-IV, CPRS-R, CGI–S, CGI–I, PGA and the ADHD Impact Module-Child (AIM-C) [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The profile of the sample (n = 171) was as follows: mean age 9.4 years (SD 1.9); 71% male; 79% White Caucasian, 12% African American, 9% other ethnicity; duration of ADHD = 3.6 years (SD 2.1); ADHD type: 77% combined, 21% inattentive, 2% hyperactive; mean ADHD-RS = 14.1 (SD 7.5); mean CPRS-R = 77.1 (SD 45.4) [see Arnold et al [25] for more details].…”
Section: Clinical Trial Populationmentioning
confidence: 99%
“…The utility values that had been determined for levels of CGI-S could then be used to estimate utilities for CGI-I based on the mapping function. The estimation of the mapping function was based on data from two clinical trials, [25,30] which were combined for this analysis. CGI-S values at follow-up were estimated using a linear regression of CGI-S scores (range 1-7) on ADHD-RS at baseline for the combined trials.…”
Section: Health State Valuationmentioning
confidence: 99%
See 1 more Smart Citation